Digital Promotion Strategy and Book Content Quality Mediated by Value Creation on Purchase Decisions of Islamic Non-Fiction Books at Elex Media Komputindo Publisher - Hediansyah; Pranowo, Agus Setyo; Hannan, Sufrin (International Journal Administration, Business & Organization, 2025)
This study examines how value creation mediates the influence of digital promotion strategy and book content quality on purchase decisions of Islamic non-fiction books published by Elex Media Komputindo. The research is grounded in the phenomenon of shifting reader behavior in the digital era, where consumers increasingly rely on online platforms to discover, evaluate, and purchase books. Despite the growth of digital channels, publishers continue to face declining performance of newly released titles, while older titles dominate sales. This indicates that existing promotional efforts have not fully succeeded in strengthening perceived value for new publications. At the same time, the abundance of book choices and intense competition among publishers make readers more selective, placing greater emphasis on both the relevance and credibility of book content. These challenges highlight the need for publishers to employ more effective digital promotion strategies and to enhance content quality in order to build stronger perceived value among consumers. By analyzing the relationships among these variables, this study aims to provide insights into how digital promotion and content quality can work in synergy to increase consumers’ perceived value and ultimately encourage purchase decisions for Islamic non-fiction books.